Odpowiedzi

2009-12-02T16:37:39+01:00
( 8 - 1 3/7 * 4 2/3 ) : 1 1/6 = (8- 20/3): 7/6= (8-6 2/3):7/6=
=1 1/3 : 7/6= 4/3*6/7= 24/21= 1.3/21= 1.1/7
2009-12-02T16:46:08+01:00
(8-1 3/7 * 4 2/3) : 1 1/16 = (8- 140/9) : 1 1/6 = (7 9/9 -15 5/9)= (- 8 4/9) : 1 1/6 = (-140/9) * 6/7 = (-13 1 /3)
tu wyżej gdzie masz (-140/9) * 6/7 to tam skracamy 9 i 6 przez 3 ,
a 140 i 7 przez 7 ;] PROSZE
  • Użytkownik Zadane
2009-12-02T20:12:47+01:00
( 8 - 1 3/7 * 4 2/3 ) : 1 1/6 = ( 8 - 10/7 * 14/3 ) : 1 1/6 = ( 8 - 20/3 ) : 7/6 = ( 8 - 6 2/3 ) : 7/6 = 4/3 * 6/7 = 24/21 = 8/7 = 1 1/7